Turnover Intention: The Impact of Ethical Climate, Job Satisfaction and Organizational Commitment - Nurtati Nurtati; Novia Yanti; Mayang Trianindi Untari (UIN Raden Mas Said Surakarta, 2020)
Human resources have a major role in every activity of the company and are essential to support the success of the organization. It can be damaged directly by employee behavior of intention to turnover. The purpose of this study was to examine the effect of the ethical climate, job satisfaction and organizational commitment on turnover intention. The research method is quantitative with a cross-sectional survey design. Data analysis uses multiple linear regression test. Three hypothesis ware tests and the results showed that thare is a significant relationship between the ethical climate and turnover intention, job satisfaction has a significant relationship with turnover intention, also organizational commitment has a significant effect on the turnover intention of employees. To reduce the risk of turnover intention the company needs to take preventive steps by building a positive work ethic climate, providing rewards. Besides improving the working atmosphere, giving attention, respect, and appreciation to all employees without discriminating the status, expertise and educational background by providing equal opportunities in the promotion of career paths.